Формирование сценографии оперетты в азербайджанском искусстве - Гусейнова, С. (Культура народов Причерноморья, 2013)
На примере развития оперетты как отдельного жанра в статье рассматривается развитие искусства сценографии. Рассматриваются основные вехи становления и развития сценического искусства на примере развития и становления Азербайджанского театра музыкальной комедии. Данная тема является актуальной для азербайджанского искусствоведения ввиду того, что она долгое время находилась в своеобразном исследовательском вакууме. В научном исследовании автор указывает на то, что искусство развивалось весьма динамично, однако искусство сценографии еще не оформилось в отдельное течение, носило субъективный, аскетичный, близкий к классическому характер. Отправной точкой развития искусства оперетты и декорирования сцены автор считает постановку оперетты «Муж и жена» азербайджанским композитором Узеиром Гаджибековым в 1909–м году. Автор подчеркивает, что эстетические выразительные средства театра меняются в связи со временем, условиями, идеологическими проблемами, морально–этическими нормами. На прикладі розвитку оперети як окремого жанру в статті розглядається розвиток мистецтва сценографії, основні віхи становлення та розвитку сценічного мистецтва на прикладі розвитку і становлення Азербайджанського театру музичної комедії. Ця тема є актуальною для азербайджанського мистецтвознавства тому, що вона довгий час перебувала у своєрідному дослідницькому вакуумі. У науковому дослідженні автор вказує на те, що мистецтво розвивалося досить динамічно, однак мистецтво сценографії ще не було окремим напрямком, мало суб'єктивний, аскетичний, близький до класичного характер. Відправною точкою розвитку мистецтва оперети та декорування сцени автор вважає постановку оперети «Чоловік і дружина» азербайджанським композитором Узеіром Гаджибековим в 1909 –му році. Автор підкреслює, що естетичні виражальні засоби театру змінюються у зв'язку з часом, умовами, ідеологічними проблемами, морально–етичними нормами. In the article by the example of the development the operetta as a separate genre the evolution of the art of the scenography is shown. The basic stages of the formation and development of the scenography are described through the formation and establishment of the Azerbaijan Theater of Musical Comedy. Due to the fact that this theme during long time was in a kind of research vacuum, this topic is an issue of current importance for the Azerbaijani art. In the study the author points out that the art was developing very rapidly, but the art of scenography as a separate trend did not yet take its shape and was subjective, ascetic and close to the classic character: the décor was elementary and primitive, the costumes and makeup were made by actors. The author highlights the following issues that the art of theater was to overcome on the way of its development: the lack of well–coordinated work of directors, screenwriters and decorators, the lack of arts critics. At that time the main driving force for the art was the word and voice. Because of the innate talent of orator, singer and reciter the actor could keep the audience in suspense, but the scenery and his appearance were at a lower level of the development. The starting point for the development of operetta and the art of scenography from the author’s point of view is the staging of the operetta “Husband and Wife” by Azerbaijani composer Uzeyir Hajibeyov in 1909. This stage work called by the author “Husband and Wife” was made in the new genre of musical comedy. The art of scenography along with the work of the actor and director became the way to visualize the dramatic text in the space and time of the perfomance, to build “the situation of the statements” and the method for determining the meaning of the perfomance. The author emphasizes that the aesthetic means of expression of the theater are changing in connection with the times, conditions, ideological issues, moral and ethical standards. On the one hand new topics require the use of new forms, styles, trends, improvement of the stage design, and on the other – deep and detailed studying of them.